Performance of DRMRIJ-31 (Giriraj) variety of mustard in cluster front line demonstration under arid climate condition: Performance of DRMRIJ-31 (Giriraj) variety of mustard in cluster front line demonstration under arid climate condition - R R MEGHWAL; B S RATHOR (Journal of Oilseeds Research, 2020)
In the Rajasthan, the average productivity is low as compared to other mustard growing area due to use of traditional method without improved variety. KVK Jodhpur had conducted cluster frontline demonstrations on mustard variety Giriraj at various villages of Jodhpur during rabi season (2016-17, 2017-18 and 2018-19). The results revealed that yield increases from 21 to 40 per cent and additional return up to `8741/ha in demonstration field compared to farmers’ practice. An extension gap ranging from 339 to 571 kg/ha was observed in the CFLD and farmers practicerespectively.